2010
DOI: 10.1094/phyto-05-10-0142
|View full text |Cite
|
Sign up to set email alerts
|

Plant Height Affects Fusarium Crown Rot Severity in Wheat

Abstract: Effects of plant height on Fusarium crown rot (FCR) disease severity were investigated using 12 pairs of near-isogenic lines (NILs) for six different reduced height (Rht) genes in wheat. The dwarf isolines all gave better FCR resistance when compared with their respective tall counterparts, although the Rht genes involved in these NILs are located on several different chromosomes. Treating plants with exogenous gibberellin increased FCR severity as well as seedling lengths in all of the isolines tested. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 26 publications
5
37
0
1
Order By: Relevance
“…Clearly, crown and spikes have different structures and they are also exposed to different microenvironments (temperature and humidity) due to their different distances from the soil surface. Previous studies showed that these factors affect the development of both FHB [25] and FCR [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Clearly, crown and spikes have different structures and they are also exposed to different microenvironments (temperature and humidity) due to their different distances from the soil surface. Previous studies showed that these factors affect the development of both FHB [25] and FCR [26]. …”
Section: Discussionmentioning
confidence: 99%
“…This is not only because only two isolines are involved for assessing the effect of a particular allele in a particular genetic background, but also because the genetic background determining morphological and phenological characters commonly influencing phenotypic assessments of quantitative traits is essentially fixed in NILs (Pumphrey et al 2007). For these reasons, NILs have been used intensively for investigating the effects of various genes of interest (Miedaner and Voss 2008;Liu et al 2010). NIL-derived populations, segregating primarily for a targeted locus, allow the conversion of a quantitative trait into a Mendelian factor, making the accurate location of a QTL possible .…”
Section: Introductionmentioning
confidence: 99%
“…Results from previous studies also show that all Rht genes, including those non-GA-responsive ones, affect FCR in wheat [12,18]. There is no ‘cause-and-effect’ that can be implied at this stage yet.…”
Section: Discussionmentioning
confidence: 91%
“…Many previous studies show that Rht genes, which may or may not produce DELLA proteins, co-locate with QTL conferring Fusarium head blight (FHB) and Fusarium crown rot (FCR) resistance [7-9]. Considering that accurate assessments for both FCR [10] and FHB [7] are difficult and that resistances to these diseases can be affected by many characteristics including plant height [11,12] and growth rate [13] which often segregate in populations used for QTL mapping, it is not difficult to understand why not all plant height QTL are coincident with those for FHB or FCR susceptibility [14,15]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation